New coumarin derivative with potential antioxidant activity: Synthesis, DNA binding and in silico studies (Docking, MD, ADMET) - Kecel-Gunduz, Serda; Budama-Kilinc, Yasemin; Bicak, Bilge; Gok, Bahar; Belmen, Burcu; Aydogan, Feray; Yolacan, Cigdem (SCIENTIFIC SCHOLAR LLC, 2023)
A new coumarin derivative, 7-((8-(4-benzylpiperidin-1-yl)octyl)oxy)-4-methyl-2H- chromen-2-one (C3), was synthesized by two-step alkylation reaction of 7-hydroxy-4-methyl cou-marin. The structure and purity of the compound were characterized by its 1H and 13C NMR, FT-IR and LC-MS spectral data. The DNA binding interaction of C3 was evaluated using UV-vis spec-trophotometric and viscosimetric methods. These experiments showed that C3 was bound in intercala-tive mode. The antioxidant activity of C3 was evaluated by the DPPH method, the antioxidant activity results displayed that C3 had DPPH radical scavenging effect. The possible mechanism of antioxidant and anticancer activity of C3 was investigated via molecular docking by using two enzymes CYP450 and EGFR as receptors. The C3 also tended a good antioxidant ability based on the result of the molecular docking analysis, with good binding affinity values (-7.82 kcal/mol) and binding site inter-actions. Molecular Dynamics (MD) simulation was implemented to elucidate the interactions with the protein-ligand complex in 20 ns. The ADMET analyzes which paved the way for us to predict C3 as a drug candidate were also performed. All experimental and theoretical results showed that the com-pound C3 was a potential drug candidate as an antioxidant and anticancer agent.(c) 2022 The Author(s). Published by Elsevier B.V. on behalf of King Saud University. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).
Keywords: Antioxidants; Synthesis design; DNA; Molecular dynamics; ADMET; CALF THYMUS DNA; DENSITY-FUNCTIONAL THEORY; FT-RAMAN SPECTRA; MOLECULAR DOCKING; ANTICANCER ACTIVITY; SPECTROSCOPIC CHARACTERIZATION; COPPER(II) COMPLEXES; VIBRATIONAL-SPECTRA; VITRO ANTIOXIDANT; CRYSTAL-STRUCTURE; Chemistry